Giant Cell Myocarditis Diagnosed at Autopsy: Case Series - Buğra, Aytül; Daş, Taner (The Bulletin of Legal Medicine, 2023)
Objective: In our study, we aimed to determine the accompanying cardiac pathologies and accompanying findings in other organs in the cases of giant cell myocarditis.Methods: The histopathology reports of autopsied cases between 2011 and 2020 were reviewed. Cases diagnosed with myocarditis were evaluated retrospectively according to their histopathological pattern. According to histopathological pattern, it was divided into subgroups as neutrophilic, lymphocytic, lymphohistiocytic, eosinophilic, myocarditis accompanied by granulomas, and giant cell myocarditis. Age and gender distribution, death patterns, autopsy findings, concomitant cardiac pathologies, and histopathological findings in other organs of cases diagnosed with giant cell myocarditis were evaluated retrospectively.Results: Between 2011 and 2020, 558 of 49,612 autopsies performed in Morgue Department of the Council of Forensic Medicine were diagnosed as myocarditis in the histopathological examination. 1.02% (n=6) were giant cell myocarditis. Three of the cases with giant cell myocarditis were male and three were female. Histopathological findings were similar in all cases diagnosed with giant cell myocarditis. The mean age was found to be 55.66 (31-80). Heart weight ranged from 433-740 gram. Mononuclear cells, polymorphonuclear leukocytes and, eosinophils accompanying giant cells were seen in the inflammatory infiltrate with necrosis. On macroscopic examination, variegated discoloration and scarring on the ventricular wall was the most common finding. Giant cell myocarditis resulted was the cause of death in four cases. Lobular pneumonia was observed in the lungs in two cases. One case had acalculous cholecystitis.Conclusion: Autopsy and histopathological diagnosis in sudden and unexpected deaths gain importance to diagnose giant cell myocarditis.
Keywords: Giant Cell Myocarditis; Sudden Death; Autopsy